New theories of mind and their implications for researching histories. Issue 3 (3rd July 2019) - Jones, Adrian
ABSTRACT: By considering new scholarship on the social distribution of cognition, artificial intelligence (AI) and philosophies of mind, this article suggests another epistemology for research in history. The contrast of new models of AI with old existentialist phenomenologies of being-in-time now suggests how meaningful action can operate without representations. These issues affect research in history. 'Picturing' theories of mind grounding Historicist and Poststructuralist academic historiographies are here re-appraised against these new trends. History research is found to be also now a quasi-ethnographic 'ontological' study of life-worlds in past being. The new epistemology I suggest here is a hermeneutic of inferences of descriptive disclosure of situated human predicaments.